The Mediating Role of Digital Competence in the Associations Between the Factors Affecting Healthcare Utilization and Access to Care - Tarja Heponiemi; Anu-Marja Kaihlanen; Lotta Virtanen; Emma Kainiemi; Petra Saukkonen; Päivikki Koponen; Seppo Koskinen; Marko Elovainio; Marko Elovainio (Frontiers Media S.A., 2024)
Objectives: To examine with a population-based longitudinal survey design whether poor health, longstanding activity limitation, impaired cognitive functioning, mental distress, or loneliness predict poor access to healthcare and whether digital competence mediates these associations.Methods: The data were from the longitudinal FinHealth -survey gathered in Finland in 2017 and 2020 including 3,771 respondents (57.1% women). Linear regression analyses were used to examine the associations of factors affecting healthcare utilization with access to care adjusted for age, sex, and education. Counterfactual causal mediation framework was used to examine the mediating role of digital competence in the relationships among these factors and access to healthcare.Results: Factors affecting healthcare utilization were associated with poor access to care and these associations were partly mediated by low digital competence. Low digital competence mediated 12%, 9% and 8%, of the associations of impaired cognitive functioning, longstanding activity limitation, and loneliness with poor access to care, respectively.Conclusion: According to our results, one way to improve the access to healthcare among vulnerable groups could be to improve their digital competence.